Propensity‐matched comparison of antiplatelet versus anticoagulant after left atrial appendage closure with the Watchman. Issue 11 (9th September 2020) - Liu, Xiao‐Xia; Kleinecke, Caroline; Busch, Sonia; Allakkis, Wasim; Mohrez, Yamen; Cheikh‐Ibrahim, Mohammad; Mahnkopf, Christian; Brachmann, Johannes; Schnupp, Steffen; Gloekler, Steffen; Yu, Jiangtao; Ma, Changsheng
Abstract: Background: Optimal antithrombotic therapy following left atrial appendage closure (LAAC) with the Watchman occluder remains uncertain. This study retrospectively compared clinical outcomes of a 3‐month dual antiplatelet therapy (DAPT group) and a protocol of anticoagulation plus aspirin for 45 days followed by DAPT for 6 months (ACT group) after LAAC with the Watchman device. Methods: Of two Watchman registries (Coburg and Lichtenfels hospitals, Germany), 220 and 304 consecutive patients with successful LAAC were included. Patients in Coburg hospital received DAPT while they received ACT in Lichtenfels. After a 1:1 propensity score matching, 174 (DAPT) versus 174 (ACT) patients were compared by use of the primary efficacy endpoint of thromboembolic events and cardiovascular/unexplained death, the primary safety endpoint of nonprocedural related major bleeding events at follow‐up, and the combined hazard endpoint, a composite of all above‐mentioned hazards. Results: The mean age 77.5 ± 7.2 (DAPT) versus 77.3 ± 7.1 (ACT) years, CHA2 DS2 ‐VASc score 4.6 ± 1.5 versus 4.7 ± 1.6, and HAS‐BLED score 3.3 ± 0.8 versus 3.3 ± 0.8 were similar. After 12 months, the clinical efficacy (13/174, 7.4% [DAPT] vs 11/174, 6.3% [ACT]; hazard ratio [HR], 0.84; 95% confidence interval [CI], 0.38‐1.86; P = .66) and safety (6/174, 3.4% vs 8/174, 4.5%; HR, 0.86; 95% CI, 0.29‐2.56; P = .79) as well as the combined hazard endpoint (18/174, 10.3% vs 18/174, 10.3%; HR, 1.01; 95% CI, 0.53‐1.95; P = .97) were comparable. Conclusions: This study suggests comparable efficacy and safety of 3‐month DAPT versus 6 weeks ACT plus aspirin following LAAC with the Watchman.